Looking Through the Entrepreneurial Kaleidoscope—Examining Stereotypes Against Commercial, Social, Environmental, and Community Entrepreneurs in Kenya and Germany - Philipp Kruse; Pauline Wangari Kamau (Administrative Sciences)
For the greater part of entrepreneurial history, entrepreneurship’s primary target was commercial, i.e., money generation for the entrepreneur and his or her stakeholders. However, starting in the 1980s, hybrid forms of entrepreneurship fusing the creation of non-financial value with entrepreneurial means have gained traction. Currently, several conceptually different forms, e.g., social, environmental, and community entrepreneurship, exist. Research yields various differences comparing commercial and hybrid entrepreneurship, particularly in the stereotypical perceptions of different entrepreneurs. Notwithstanding notable insights, entrepreneurial stereotype research suffers from three major shortcomings. First, stereotype differences are primarily examined by comparing commercial to hybrid entrepreneurs, neglecting stereotype differences inside hybrid entrepreneurship. Second, the scope of stereotypes investigated (e.g., warmth and competence) remains vague and lacks entrepreneurial specificity. Third, the robustness of entrepreneurial stereotypes under different institutional circumstances, e.g., in economy and culture, is unclear. The current study addresses these three shortcomings. Analyzing two samples from Kenya and Germany (Ntotal = 286) with repeated-measures analyses of co-variance, we find notable stereotype differences (i) inside hybrid entrepreneurs; (ii) regarding warmth, competence, and entrepreneurship-specific success indicators; and (iii) under different institutional circumstances. Despite acknowledgeable limitations, our work extends previous stereotype research by highlighting the necessity for a more fine-grained, specific, and inter-country perspective on entrepreneurial stereotypes.